2013
DOI: 10.1016/j.ergon.2012.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Pilot task-based assessment of noise levels among firefighters

Abstract: PURPOSE Over one million American firefighters are routinely exposed to various occupational hazards agents. While efforts have been made to identify and reduce some causes of injuries and illnesses among firefighters, relatively little has been done to evaluate and understand occupational noise exposures in this group. The purpose of this pilot study was to apply a task-based noise exposure assessment methodology to firefighting operations to evaluate potential noise exposure sources, and to use collected tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
(55 reference statements)
1
7
0
Order By: Relevance
“…Firefighter training noise exposures were comparable to those we have previously documented in firefighting activity (Neitzel et al, 2013). Measurements from these and other studies (Kirkham et al, 2011; Tubbs, 1992) demonstrate the potential for exposure >85 dBA, the NIOSH recommended limit, suggesting increased risk of NIHL.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Firefighter training noise exposures were comparable to those we have previously documented in firefighting activity (Neitzel et al, 2013). Measurements from these and other studies (Kirkham et al, 2011; Tubbs, 1992) demonstrate the potential for exposure >85 dBA, the NIOSH recommended limit, suggesting increased risk of NIHL.…”
Section: Discussionsupporting
confidence: 75%
“…Noise exposures have not been well-studied among firefighters, but the limited existing data suggest that exposures may be widespread (Tubbs, 1995), specifically during emergency response and training operations (Kales et al, 2001; Neitzel et al, 2013). Neitzel et al (2013) demonstrated potential for exposure >85 dBA, the full-shift Time-Weighted Average (TWA) limit recommended by the US National Institute for Occupational Safety and Health (NIOSH), and found that the highest levels were associated with saws and pneumatic chisels (Neitzel et al, 2013). For reference, 60 dBA is approximately as loud as normal speech at arm's length, 85 dBA is about as loud as a gasoline-powered lawnmower, and 100 dBA is roughly as loud as a motorcycle.…”
Section: Introductionmentioning
confidence: 99%
“…Firefighters can be exposed to a short-term, high level of noise during their emergency operations (e.g. sirens and using extraction equipment) (Neitzel et al 2013). However, we observed during the current study that firefighters regularly wore headsets with a dual function of noise protection and internal communication on fire trucks and engines when they responded to calls.…”
Section: Discussionmentioning
confidence: 99%
“…These self-reported noise exposures are congruent with the literature. Neitzel et al (2013) reported that firefighter task-based noise levels ranged from 82 dBA to 109 dBA, and the majority of estimated 8-hour and 24-hour noise exposures exceeded recommended exposure limits. Root et al (2013) also found that commonly used fire station equipment (i.e., lawn maintenance equipment, snow blowers, compressors, and emergency alarms) and equipment on the fire engines (i.e., fans, saws, alarms, and extrication equipment) emitted noise equal to or greater than 85 dBA.…”
Section: Discussionmentioning
confidence: 99%
“…Firefighters are routinely exposed to occupational noise from a variety of firefighting tasks and equipment, such as the use of saws and pneumatic chisels (Neitzel, Hong, Quinlan, & Hulea, 2013). Construction workers in the operating engineer trade are also exposed to a noise level above 85 dB (loud enough to cause hearing loss) when they operate heavy equipment (e.g., bulldozers, graders, backhoes, asphalt road rollers, asphalt spreaders, and wheel loaders; Kerr, Brosseau, & Johnson, 2002; Legris & Poulin, 1998).…”
mentioning
confidence: 99%